Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/plants9091198
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Induced Polymorphism in SD1 Gene Governing Semi-Dwarfism in Rice and Development of a Functional Marker for Marker-Assisted Selection

Abstract: The semi-dwarfing allele, sd1-d, has been widely utilized in developing high-yielding rice cultivars across the world. Originally identified from the rice cultivar Dee-Geo-Woo-Gen (DGWG), sd1-d, derived from a spontaneous mutation, has a 383-bp deletion in the SD1 gene. To date, as many as seven alleles of the SD1 gene have been identified and used in rice improvement, either with a functional single-nucleotide polymorphism (SNP), with insertion–deletions (InDels), or both. Here, we report discovery of a novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Few studies have attempted to analyze the metabolite diversity of different Chakhao rice types in North East India [29,30] but no studies have attempted to profile their aroma.…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have attempted to analyze the metabolite diversity of different Chakhao rice types in North East India [29,30] but no studies have attempted to profile their aroma.…”
Section: Resultsmentioning
confidence: 99%
“…After pyramiding the favorable alleles located on these five loci into a single genotype, the PH could be reduced by −30.57 cm. A moderate plant height is an important basis for rice breeding, and this is supported by Andrew-Peter-Leon, et al [ 40 ] and Bhuvaneswari, et al [ 41 ], who have reported that OsGA20ox2 and OsFBX26 , have important roles in regulating semi-dwarfism and early flowering in rice. Likewise, this finding is supported by Liu, et al [ 29 ], who reported that several semi-dwarf rice varieties have been bred by genetic introduction of the mutant alleles of SD1, which encodes OsGA20ox2 for catalyzing GA biosynthesis.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies in rice plants indicate that the reduced height of the sd-1 is due to the defect in the GA biosynthetic pathway [ 6 , 47 , 48 ], as opposed to the wheat Rht-B1/Rht-D1mutant plants in which the GA signal transduction pathway is weakened [ 49 , 50 ]. Importantly, the OsGA20ox gene corresponds to the Sd-1 locus in the rice genome [ 41 , 51 ]. Similar results were found by Liu, et al [ 29 ], who reported that the culm content of bioactive gibberellin, especially in the basal internodes, is reduced by a semi-dominant lodging resistance gene, SBI , which encodes a culm-specific expressed OsGA2ox , and, thereafter, the higher activity of the SBI considerably reduced the rice PH and contributed to breed enhanced lodging resistant rice varieties and, therefore, increased the yield.…”
Section: Discussionmentioning
confidence: 99%
“…Many dwarfing mutants have been found in important food crops such as maize, wheat, and rice [6,7]. Among them, more than 90 dwarfing genes in rice, 26 in wheat, and 20 in maize were identified by using dwarfing materials, such as predominant semidwarf1 (sd1) [8], shortened basal internodes (SBI) [9], reduced height genes Rht-B1b, Rht-D1b and Rht18 [10,11], and brassinolide biosynthesis inhibitor BRI1 [12].…”
Section: Introductionmentioning
confidence: 99%